New Collaborative Working Environments 2020 - Stewing, Franz-Josef; Heimann, Erik (2006)
In January and February 2006, New Working Environments Unit of the Directorate General information Society and Media of the European commission organised two workshops where recognised experts in the field discussed the most outstanding research themes that will affect the R&D agenda in the Collaborative Environments (CE) area in FP7 (2007-2013). The workshop in January gathered members of the Collaboration@work Experts Group representing academia and research departments within IT industry. The workshop in February got together mainly IT industry representatives directly related to the business of their companies and not only to research, with the support of 5 representatives of academia. This publication encompass the findings coming out of both workshops summarising the vision, characteristics and research challenges brought forward by the experts. The first section of this document is dedicated to the IT industry perspectives on CE supporting Business and Industry. The second section includes the vision and challenges for Collaborative Environments 2020 drawn by the Collaboration@work Experts Group.